Primary care management of patients who self-harm. - Allan, C; Behrman, S; Ebmeier, K (2012)
Self-harm is best defined as 'any act of self-poisoning or self-injury carried out by an individual irrespective of motivation'. With a 10.5% lifetime risk, self-reported self-harm is common in the community. Self-harm can occur at any age but is most common in young people. Prior self-harm is the key risk factor both for repeated self-harm and also for subsequent suicide. The presence of depressive symptoms predicts repeated self-harm, as does any history of psychiatric illness. Assessment of self-harm (actual or planned) should include: details of preplanning; final acts; the event itself; what happened afterwards; as well as broader psychosocial risk factors. Patients should be asked to reflect on the episode to consider whether they regret it, or whether they are likely to repeat it. Patients should be screened for depression, anxiety, psychosis and history of self-harm. Physical illness and substance misuse increase risk. Referral to secondary care community mental health teams should be considered for patients who present in primary care with a history of self-harm and a risk of repetition. Patients with continuing thoughts or serious intent of self-harm, where supportive or protective factors cannot be identified, may need urgent referral to secondary care. Prediction of further episodes of self-harm is difficult. Some clinicians may find the use of standardised rating scales, such as the SAD PERSONS scale, a useful way to identify patients who warrant referral and further assessment. The GP should provide long-term continuity of care, and maintain a holistic awareness of a patient's life events enabling discussion of the patient's emotional problems at an early stage with the aim of intervening before a crisis.